Clinical InvestigationsCase series analysis of post-brachytherapy prostate edema and its relevance to post-implant dosimetry. Post-implant prostate edema and dosimetry - Tejwani, Ajay; Bieniek, Eva; Puckett, Lindsay; Lavaf, Amir; Guirguis, Adel; Bennish, Aaron; Ashamalla, Hani (Journal of Contemporary Brachytherapy, 2012)
Purpose : We evaluated the post-operative pattern of prostate volume (PV) changes following prostate brachytherapy (PB) and analyzed variables which affect swelling. Material and methods: Twenty-nine patients treated with brachytherapy (14) or combined brachytherapy and external beam radiotherapy modality (15) underwent pre- and post-implant computed tomography (CT). Prostate volume measurements were done on post-operative days 1, 9, 30, and 60. An observer performed 139 prostate volume (PV) measurements. We analyzed the influence of pre-implant PV, number of needles and insertion attempts, number and activity of seeds, Gleason score, use of hormonal therapy and external beam radiation therapy on the extent of edema. We computed a volume correction factor (CF) to account for dosimetric changes between day 1 and day 30. Using the calculated CF, the dose received by 90% (D 90 ) of the prostate on day 30 (D 90 Day30) was obtained by dividing day 1 (D90Day1) by the CF. Results: The mean PV recorded on post-operative day 1 was 67.7 cm 3 , 18.8 cm 3 greater than average pre-op value (SD 15.6 cm 3 ). Swelling returned to pre-implant volume by day 30. Seed activity, treatment modality, and Gleason score were significant variables. The calculated CF was 0.76. After assessment using the CF, the mean difference between estimated and actual D 90 Day30 was not significant. Conclusions : We observed maximum prostate size on post-operative day 1, returning to pre-implant volume by day 30. This suggests that post-implant dosimetry should be obtained on or after post-operative day 30. If necessary, day 30 dosimetry can be estimated by dividing D 90 Day1 by a correction factor of 0.76.